1997
DOI: 10.1523/jneurosci.17-13-05155.1997
|View full text |Cite
|
Sign up to set email alerts
|

Brain Aging: Changes in the Nature of Information Coding by the Hippocampus

Abstract: Advanced age in rats is associated with a decline in spatial memory capacities dependent on hippocampal processing. As yet, however, little is known about the nature of age-related alterations in the information encoded by the hippocampus. Young rats and aged rats identified as intact or impaired in spatial learning capacity were trained on a radial arm maze task, and then multiple parameters of the environmental cues were manipulated to characterize the changes in firing patterns of hippocampal neurons corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
100
5
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 156 publications
(119 citation statements)
references
References 44 publications
(59 reference statements)
10
100
5
1
Order By: Relevance
“…Aged rats are impaired in spatial learning, although the severity of the deficit is highly variable (Barnes, 1988(Barnes, , 1994DeToledo-Morrell et al, 1988;Gage et al, 1988;Markowska et al, 1989;Rapp and Amaral, 1992;Gallagher and Nicolle, 1993;Rapp and Heindel, 1994). Previous studies on place cells in aged rats have reported that their spatial specificity may decrease with age (Barnes et al, 1983), but other recent studies, including our own, have failed to confirm any clear association between place field specificity and impaired spatial learning in aged animals (Mizumori et al, 1996;Tanila et al, 1997). However, all of the electrophysiological studies were conducted using environments that were highly familiar to the animals, whereas virtually all the studies that demonstrate the age-related spatial impairment focus on learning new spatial environments.…”
Section: Abstract: Aging; Hippocampus; Place Field; Spatial Learningmentioning
confidence: 62%
See 2 more Smart Citations
“…Aged rats are impaired in spatial learning, although the severity of the deficit is highly variable (Barnes, 1988(Barnes, , 1994DeToledo-Morrell et al, 1988;Gage et al, 1988;Markowska et al, 1989;Rapp and Amaral, 1992;Gallagher and Nicolle, 1993;Rapp and Heindel, 1994). Previous studies on place cells in aged rats have reported that their spatial specificity may decrease with age (Barnes et al, 1983), but other recent studies, including our own, have failed to confirm any clear association between place field specificity and impaired spatial learning in aged animals (Mizumori et al, 1996;Tanila et al, 1997). However, all of the electrophysiological studies were conducted using environments that were highly familiar to the animals, whereas virtually all the studies that demonstrate the age-related spatial impairment focus on learning new spatial environments.…”
Section: Abstract: Aging; Hippocampus; Place Field; Spatial Learningmentioning
confidence: 62%
“…Three young (4 -6 months, 35-450 gm at the beginning of the recordings) and four aged (25-29 months, 450 -600 gm) male Long-Evans rats served as subjects. Rats were the same that were used in the study described in our accompanying paper (Tanila et al, 1997). The animals were individually housed from the beginning of pretraining, maintained on a 12 hr light/dark cycle, and given ad libitum access to water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, hippocampal cells show place field changes with changes in environments or the available constellation of cues [17,90,93,129,148,181,219,223,250]. Animals with learning deficits (whether by aging, NMDA-blockade, or cortical lesions) also show an instability of place fields across sessions, though not within the session itself [8,11,87,127,189,190,220,221].…”
Section: Non-spatial Place Cellsmentioning
confidence: 99%
“…Moreover, a variety of functional deficits in these structures and changes in neuronal encoding properties correlate with individual differences in spatial learning abilities [3,10,12,20,41]. However, it has been reported that minimal individual variability exists among aged male F344 rats and that variability within this and potentially other rodent models of human cognitive aging may be a result of within-subject factors rather than reliable individual differences between aged rats [3,18].…”
Section: Introductionmentioning
confidence: 99%